Security Detention in International Territorial Administrations: Kosovo, East Timor, and Iraq - Direk, Omer Faruk (Brill Nijhoff, 2015)
What happens after a governing body is ousted during the course of armed conflict? In some cases, international organizations like the United Nations will appoint other States or itself to administer the transition of the post-conflict State to a place of lasting peace. In practice, however, this mission is hardly linear and becomes further complicated when these administrations are faced with threats to the fragile peace. Security Detention in International Territorial Administrations examines the legal and policy questions surrounding the behavior of these post-conflict administrations. This includes discussion about apportionment of responsibility in peace support operations, norm conflict issues in UN Security Council resolutions, and requirements of international human rights law in the fulfillment of these missions. The discussion concludes with a survey of security detention practices in three recent post-conflict administrations in Kosovo, East Timor, and Iraq.